New Regulation of Direct Foreign Investment Screening in the European Union and Interests of Russia - L. L. Razumnova; T. E. Migaleva (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
The article deals with adoption of a new framework regulation of direct foreign investment (DFI) of the European Union in condition of shaping a polycentric system of international relations and re-balancing of global players’ forces, which is accompanied by weakening the positions of the EU on global market and strengthening China as a new superpower. In this situation the EU tries to reinforce economic security and raise competitiveness of economy by protecting the sphere of critical infrastructure and high technologies against external control. The authors provide a brief analysis of geopolitical, economic and political factors, which determined specific features of new EU investment legislation. The scale and structure of Chinese DFI in EU economy were estimated and specificity of the process of mutual outsourcing of EU and China political values was identified. According to the analysis, China that increases its presence in the EU, apart from big finance possibilities uses differentiation of priorities in foreign and home policy of member-states and internal European contradictions and fragmentation of EU legislation. By using the text of the framework Regulation 2019/452 key elements and procedures were described and contradictions in the mechanism of investment selection being designed were found. It is proved that these contradictions, including numerous different agreements and institutional units involved in the process, keeping national priorities in making final decisions in the absence of necessary for DFI screening function system elements and others hinder the creation of the efficiently functioning supranational system of European DFI control. A conclusion was drawn that introduction of the Regulation can have a negative effect on the inflow of Russian investment to Europe. At the same time Russia cannot affect designing of this screening mechanism, as its role is limited by the frameworks of European policy of partial communication isolation. In the long-term the toughness of using investment regulation in the EU will depend on the outline of the US – EU – Russia confrontation.